A taste for words and sounds: a case of lexical-gustatory and sound-gustatory synesthesia - Colizoli, Olympia; Murre, Jaap M.; Rouw, Romke (Frontiers in Psychology, 2013)
Gustatory forms of synesthesia involve the automatic and consistent experience of tastes that are triggered by non-taste related inducers. We present a case of lexical-gustatory and sound-gustatory synesthesia within one individual, SC. Most words and a subset of nonlinguistic sounds induce the experience of taste, smell and physical sensations for SC. SC’s lexical-gustatory associations were significantly more consistent than those of a group of controls. We tested for effects of presentation modality (visual vs. auditory), taste-related congruency, and synesthetic inducer-concurrent direction using a priming task. SC’s performance did not differ significantly from a trained control group. We used functional magnetic resonance imaging to investigate the neural correlates of SC’s synesthetic experiences by comparing her brain activation to the literature on brain networks related to language, music and sound processing, in addition to synesthesia. Words that induced a strong taste were contrasted to words that induced weak-to-no tastes (“tasty” vs. “tasteless” words). Brain activation was also measured during passive listening to music and environmental sounds. Brain activation patterns showed evidence that two regions are implicated in SC’s synesthetic experience of taste and smell: the left anterior insula and left superior parietal lobe. Anterior insula activation may reflect the synesthetic taste experience. The superior parietal lobe is proposed to be involved in binding sensory information across sub-types of synesthetes. We conclude that SC’s synesthesia is genuine and reflected in her brain activation. The type of inducer (visual-lexical, auditory-lexical, and non-lexical auditory stimuli) could be differentiated based on patterns of brain activity.